Redesign Mesin Belt Sander Meja Portable dengan Metode Quality Function Deployment (QFD): Belt Sander Redesign, Portable, Quality Function Deployment (QFD), House of Quality (HoQ) - Andrew Sabbathinus Putra Subagio, Andrew; Riandadari, Dyah; Mahendra Sakti, Arya; Nugroho, Aji (Jurnal Rekayasa Mesin, 2026)
Rapid technological developments demand increased efficiency and productivity in various industrial sectors, including the woodcraft industry. The sanding process, which is generally still done manually, results in long processing times and inconsistent results. Belt sanders are a solution to increase efficiency, but most designs in circulation are still large and stationary, making them less suitable for use by small businesses or home workshops. This study aims to redesign a portable benchtop belt sander using the Quality Function Deployment (QFD) method to ensure the resulting design meets consumer needs and desires. Through the QFD method, the voice of the customer is translated into technical product characteristics using the House of Quality (HoQ) matrix. The research method used is quantitative with a product design approach based on the Ulrich and Eppinger model, which includes four stages: planning, development, design, and detailed design. Data analysis is carried out through instrument validity and reliability tests, and processing of QFD results to determine key technical specifications. The results of this study are expected to produce a portable benchtop belt sander design that has better ergonomics, high flexibility, and is able to increase sanding process efficiency for small to medium-scale users.